ANALYSIS OF RADON GAS EXPOSURE IN THE HOME ON THE RISK OF LUNG CANCER (NARRATIVE REVIEW) - Adinda Wanodya Sulthanah; Dewi Utami Iriani (Journal of Community Health and Preventive Medicine, 2022)
According to WHO 2009, exposure to radon gas is known to be the second highest cause of lung cancer. The United States Environmental Protection Agency (U.S.EPA) estimates that 21,000 lung cancer deaths annually result from exposure to radon in the United States. Radon (ð‘…ð‘›222) naturally originates in soil and rock and it is the decay of Uranium-238 (ð‘ˆ 238). This study used a literature review study that aims to review several research journal articles regarding exposure to Radon gas in the home with the risk of lung cancer. The data base used to search for research journal articles are Science Direct, PubMed, DOAJ, JSTOR, and Taylor & Francis. The results of this study were: (1) nine out of twelve journal articles described a significant association between Rn in the home (concentration of Rn 37 Bq/ð‘š3 until â‰¥ 300 Bq/ð‘š3 ) and the risk of lung cancer; (2) the duration of stay of the occupants in the house lasted from 2-30 years; and (3) eight journal articles presented that the most common lung cancer cell subtype associated with Rn exposure in the home was adenocarcinoma and squamous cell carcinoma. People need to maintain indoor airflow and choosing safe building material (not containing Rn).